Degradation impacts on riparian forests of the lower Mearim river, eastern periphery of Amazonia - Silva, Roberto Lima da; Leite, Márcio F.A.; Muniz, Francisca Helena; Souza, Luis Augusto Gomes de; Moraes, Flávio Henrique Reis de; Gehring, Christoph (Forest Ecology and Management, 2017)
We describe degradation impacts on biomass, structural and functional composition of riparian forests of the Mearim river, eastern periphery of Amazonia, based on 40 transects from open water to terra firme and covering 4 degradation levels. Biomass was high (306.3 Mg ha−1) in original mature forests (MF), and 92.3% lower in strongly degraded (SD) sites. This suggests disproportionally high CO2-emissions via riparian forest degradation and calls for their preferential conservation and restoration to contain global warming. Degradation affected vegetation structure, especially plant size distribution, whereas overall plant abundance did not differ between degradation levels. ‘Aninga’ (Montrichardia arborescens and M. linifera) forms a conspicuous vegetation component in the aquatic zone, with 12.6% biomass and 58.4% abundance shares, relatively constant up to mid-level degradation but significantly lower in SD. Aninga's forefront position breaks the kinetic energy of waves and currents, making it ideal for erosion-control, we establish allometric equations for aninga biomass estimation. Erosion caused land-loss in the aquatic and semiaquatic sections of degraded sites. The biomass share of potentially N2-fixing Fabaceae was significantly higher in both aquatic (41.4%) and semiaquatic (44.8%) zones than in terra firme (6.3%). High denitrification N-losses in alternately aerobe-anaerobe zones could reduce N-availability and give N2-fixing legumes a competitive edge; we therefore recommend N2-fixing legumes for riparian forest restoration. We find low to moderate changes of vegetation indicators up to mid-level degradation, as opposed to systematically differing SD, pointing to a critical degradation threshold beyond which dysfunctionality impedes riparian ecosystem functioning. © 2017 Elsevier B.V.
Keywords: Biomass; Carbon; Conservation; Ecosystems; Erosion; Global Warming; Kinetics; Nitrogen Fixation; Restoration; Rivers; Vegetation; Biological Nitrogen Fixations; Carbon Stocks; Fabaceae; Montrichardia; Riverine Forest; Structural Composition; Forestry; Allometry; Biomass; Carbon Emission; Carbon Sequestration; Degradation; Denitrification; Ecosystem Function; Ecosystem Structure; Functional Role; Global Warming; Herb; Nitrogen Fixation; Nutrient Availability; Open Water; Peripheral Region; Riparian Forest; Vegetation Structure; Biomass; Carbon Dioxide; Degradation; Forests; Indicators; Amazonia; Mearim River; Fabaceae; Montrichardia; Montrichardia Arborescens; Montrichardia Linifera